Hydrometallurgical treatment of disseminated gold in pyrite and arsenopyrite - Azañero Ortiz, Angel (2009)
The ore is complex and presents abundant content of sulphurs: pyrite, arsenopyrite and pyrrhotite, also in few proportion: chalcopyrite, sphalerite and probably sulfhosals that add: copper, silver, arsenic and antimony. Free gold is not appreciated in the obtained results, the major content of gold is in tails of flotation Cu-Ag, constituted by sulphurs of iron, as a non metallic residue prevails the quartz, coal and the insolubles, it is quite strong and naturally very acid, pH:5.3. It is possible to obtain a concentrate of flotation Cu-Ag, with As and Sb like pollutants and around 80% of the total gold stays in tails, to which we effect a direct cyanidation having variant like pH and granulometry, it has not been possible to leach more than 11 % of the gold contained in tails that gives 3.2 grams Au/TM, considering the current prices it has an approximate value 100 US $ Ton.